Background commentary on the Researching the Obesogenic Food Environment (ROFE) project - Reginald Adjetey Annan; Nana Ama Frimpomaa Agyapong; Anne Marie Thow; Elizabeth Catherina Swart (Cambridge University Press, 2024)
Abstract Objective: The objective of this commentary is to provide an overview of the rationale and objectives of the Researching the Obesogenic Food Environment (ROFE) project that was conducted in Ghana and South Africa. Design: Narration has been used to describe the main objectives, phases as well as the methods used for the conduct of this project. Setting: The project described in this commentary was conducted in Khayelitsha and Mount Frere in South Africa and Ahodwo and Ejuratia for Ghana. Participant: Participants of the study described here include households in South Africa and Ghana, stakeholders and policymakers, and various actors within the food chain in both countries. Results: The ROFE findings provide a good understanding of the extent of the impact of the food environment on consumption, characteristics of value chains of healthy and unhealthy foods, as well as the potential for improved governance and policy that is relevant to the region. The supplement provides the opportunity to share the extensive findings of the ROFE project. Nine papers that describe the process and findings of the three phases of the ROFE project have been presented. Some of the papers focus on phases of the ROFE, while others cut across different phases and explore the linkages between the phases. Briefly descriptions of key findings of some of the papers in the supplement are provided. Conclusion: Together, the findings of the ROFE study presented in this supplement have increased understanding of how communities in SA and Ghana interact with their food supplies and have led to identification of specific opportunities to improve food supply policies, in ways that create incentives for the production and consumption of healthy, relative to unhealthy foods.